The Accuracy and Quality Translation of Google Translate toward Harf Al Ma'ānī in Arabic - Siti Zainab; Akhmad Saehudin; Robby Malik Al-Ummat; Shuhaila Diva Noer (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2022)
Technological developments have a major impact on human life. The existence of machine translation is the result of technological advances to make it easier for humans to translate one language into another. This research focuses on the accuracy of google translate in translating burf ma'ani in Arabic. The corpus of data that is the object of this research is a number of texts such as in the book Dalilun fi Al-Tarjamah by DR. H. Rofi'i. The method used in this study is a qualitative method (qualitative method) by comparing the google translate translation with the translation according to Arabic rules. Data collected through library research (brary research). The results showed that in terms of accuracy of vocabulary and terms, google translate has a fairly good translation quality, both in terms of clarity and fairness of meaning. However, google translate is not able to convey ideas from the source language (SL) Arabic into the target language (TL). From these data it can be seen that google translate should not be used as a basis for translating Arabic texts into Indonesian, especially in translating the verses of the harfu Ma'aniy. A novice translator should choose a dictionary instead of using google translate for business and improve translation skills.